Priming psychic and conjuring abilities of a magic demonstration influences event interpretation and random number generation biases - Mohr, Christine; Koutrakis, Nikolaos; Kuhn, Gustav (Frontiers in Psychology, 2015)
Magical ideation and belief in the paranormal is considered to represent a trait-like character; people either believe in it or not. Yet, anecdotes indicate that exposure to an anomalous event can turn sceptics into believers. This transformation is likely to be accompanied by altered cognitive functioning such as impaired judgements of event likelihood. Here, we investigated whether the exposure to an anomalous event changes individuals’ explicit traditional (religious) and non-traditional (e.g. paranormal) beliefs as well as cognitive biases that have previously been associated with non-traditional beliefs, e.g. repetition avoidance when producing random numbers in a mental dice task. In a classroom, 91 students saw a magic demonstration after their psychology lecture. Before the demonstration, half of the students were told that the performance was done respectively by a conjuror (magician group) or a psychic (psychic group). The instruction influenced participants’ explanations of the anomalous event. Participants in the magician, as compared to the psychic group, were more likely to explain the event through conjuring abilities while the reverse was true for psychic abilities. Moreover, these explanations correlated positively with their prior traditional and non-traditional beliefs. Finally, we observed that the psychic group showed more repetition avoidance than the magician group, and this effect remained the same regardless of whether assessed before or after the magic demonstration. We conclude that pre-existing beliefs and contextual suggestions both influence people’s interpretations of anomalous events and associated cognitive biases. Beliefs and associated cognitive biases are likely flexible well into adulthood and change with actual life events.